2004
DOI: 10.1097/01.aud.0000120364.13671.e2
|View full text |Cite
|
Sign up to set email alerts
|

Is Normal or Less Than Normal Overall Loudness Preferred by First-Time Hearing Aid Users?

Abstract: LessLoudn, which gave less than normal overall loudness according to the loudness model used, was preferred both in the field and in the laboratory tests. Speech recognition scores were similar for both methods. A comparison between the measured gain for NormLoudn and the gain prescribed by CAMEQ, NAL-NL1, and DSL[i/o], suggests that all three prescriptive procedures (DSL[i/o] in particular) would probably overestimate the required gain for subjects without hearing aid experience and with mild to moderate hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…Acoustic feedback may preclude the use of higher gain. Gain might be reduced to address individual listener preference (e.g., Smeds, 2004). This study only examined one measure of temporal resolution at a single frequency and masker level.…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic feedback may preclude the use of higher gain. Gain might be reduced to address individual listener preference (e.g., Smeds, 2004). This study only examined one measure of temporal resolution at a single frequency and masker level.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show positive and acceptable results (Humes, 1999;Hornsby and Ricketts, 2003); others show good speech recognition but higher loudness ratings than would be ideal (Lindley and Palmer, 1997;Alcántara et al, 2004;Smeds, 2004). Higher loudness ratings tend to be more pronounced with higher-level inputs or higher frequencies, or both.…”
Section: Outcomes For Adultsmentioning
confidence: 99%
“…In contrast, measures of loudness do not replicate this finding (Alcá ntara, et al, 2004;Smeds, 2004;Wesselkamp, et al, 2001). Smeds (2004) compared listeners' preferred gain settings out of two alternatives to prescriptive targets and found that DSL [i/o] in particular would be perceived as too loud for this group of first-time hearing aid users.…”
Section: Background and Rationalementioning
confidence: 57%
“…Smeds and colleagues (Smeds, 2004;Smeds, et al, 2006a,b) found that new hearing instrument users preferred less gain than prescribed by common prescriptive methods, including DSL[i/o]. Subsequent laboratory and real world comparisons of new and experienced hearing instrument users showed the same pattern of preferences for lower than prescribed gain, with no differences between groups.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation